Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.3 Product and Quotient Rules - Exercises - Page 121: 11


$g’(x) = \frac{-e^x}{(1+e^x)^2}$

Work Step by Step

$g(x) = \frac{1}{1+e^{x}}$ $g(x) = (1+e^{x})^{-1}$ $Power$ $Rule:$ $g’(x) = (-1)(1+e^x)^{-2}(e^x) $ $g’(x) = \frac{-e^x}{(1+e^x)^2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.